ISO 9001 and ISO 17025 standards in a metrology laboratory - Barradas, José (2011)
In the last decade, the number of companies with quality certification has increased in most countries. According to the ISO 9001 standard all the certified companies should calibrate their measuring equipment. By doing so, companies can guarantee, with rigor and quality, its measurement and use reliable data for monitoring the quality of its products and its improvement. However, a metrology laboratory is not required to hold an ISO 9001 certification or ISO 17025 accreditation. In this moment, there are companies that have metrology laboratories to conduct an internal check of their measuring equipment. These companies have their quality management systems (QMS) certified according to the ISO 9001 standard and so all its departments and sub-departments must also comply with the requirements of this standard. On the other hand there are companies with ISO 17025 accredited laboratories. Usually these companies are independent and his metrology laboratory is essentially to perform the calibration service to national companies who use their services to make the calibration of its measuring devices. These labs can be inserted into a company which does not have their certified QMS. Finally, there are companies that have an ISO 9001 QMS and also a metrology laboratory accredited by ISO 17025 standard. In this case the metrology laboratory must comply with the requirements of both standards. With this research project we intend to analyze the importance level of ISO 9001 and ISO 17025 standards for a metrology laboratory in order to reach the organizational excellence.